Grundtvigs sysler og interesser i første halvdel af 1831 - Toldberg, Helge (Grundtvig-studier, 1964)
Grundtvig3s Literary Activities during the First Half of 1831 By Helge Toldberg (Revised by Dr. Noelle Davies) Is his important thesis, Menneske først - Grundtvigs opgør med sig selv (“A Man before a Christian - the Heart-searchings of Grundtvig”, 1963), Dr. Kaj Thaning regards the year 1832 as the decisive date in the life and literary activity of Grundtvig, characterized by the drawing of a distinct dividing-line between general human activities and Christian preaching. He derives this change from influences during Grundtvig’s research visits to England in the three previous summers, particularly the effect of one night’s conversation in 1830 with Mrs. Clara Bolton, otherwise known as a friend of Disraeli’s. That he fell in love with an English lady, whoever she was, is corroborated by a number of extracts from minor poems by Byron in Grundtvig’s book of notes employed at the British Museum (v. facsimile facing P. 28 and list of entries P. 21-22 note 22). The quotation from “ The spell is broke” in the facsimile may to some extent account for the sudden disappearance of calls to repentance from Grundtvig’s sermons during the early months of 1831. After he had resigned his office as curate to Our Saviour’s Church in Copenhagen in 1826, Grundtvig provided his former churchgoers with three collections of sermons, the last one appearing in July 1831. Owing to a verdict for libel inflicted on him, all his works had to be submitted to the censor for approval, which was most annoying to Grundtvig himself, but makes it easier for modern research to ascertain when each individual work of his was in proof. The third volume of the sermons was marked with the censor’s approval on 16th March 1831, and we know from letters to a friend that the composing began by the middle of February, but that on the other hand Grundtvig was still elaborating some of his sermons at the end af April. Unfortunately Dr. Thaning has taken only the latter fact into account, and assumes that Grundtvig composed the sermon for Easter Sunday, No. 13 in the collection, on that very day of 1831. The seeming contradiction in the statements of the printer’s work is accounted for, however, in the Provisional Orders for censorship. Books exceeding 24 sheets were not liable to censorship, but the printer had to convince the censor that the book was large enough to relieve him of his duty. In the present case it appears from the typographic arrangement that 28 sheets (448 pages) were laid before the censor, which means that 19 out of the 29 sermons were set up by 16th March, whereas the last 10 sermons composed later were exempt from censorship. As a matter of fact, the latter are remarkable for a predilection for the Holy Sacraments, as Dr. Thaning has shown, and No. 20 includes a religious biography of Grundtvig, a typical sign of his opening a new epoch of his life or his way of preaching. Dr. Thaning’s assumption of a relatively late date for the Easter sermon is due to his conviction that Grundtvig’s development from Lutheran orthodoxy, even if modified by the “unparalleled discovery” of 1825, to his changed views of 1832, followed a straight course. An outstanding feature of that sermon is the comparison of Lutheranism to Christ’s Descent into Hell, whereas in the Epiphany sermon (No. 6) it is compared to the Resurrection. To Dr. Thaning, who takes it for granted that the sermons were composed according to the order of holidays in the ecclesiastical year, this is strong evidence, but it has escaped his notice that the Good Friday sermon agrees with the view of the Epiphany one. This fact is the more interesting because Good Friday is the most important holiday not served in the previous collections, and the Epiphany is another, while sermons for Maundy Thursday and Easter Sunday were already available, so that new sermons for the latter must have sprung from a deep impetus in Grundtvig at any time during the period of more than two years spent in preparing the book. As the tendency to provide the reader with sermons for neglected holidays is predominant towards the end of the volume, it would be more natural to conceive of the sermons for the Epiphany and Good Friday as written in the very nick of time before the printing to comply with this demand. Moreover, a close examination of the two other Easter sermons favours their originating from the autumn of 1829. Just then Grundtvig was considering the possibility of emigrating, which is also suggested in the sermon for Easter Sunday, while the one for Maundy Thursday presents a slightly contemptuous comparison of the narrow waterway leading to Copenhagen and the big seas, a conception for which one visit to England would suffice. Finally the strong emphasis on the Descent in the former points to a connection with No. 9, “ Christ’s Descent into Hell”, which draws on entries regarding Middle English works derived from The Gospel of Nicodemus made in Grundtvig’s book of English notes in 1829, as we^ as on extracts from the Holy Fathers made after his return that year, in order to refute doubts of the Descent being an original part of the Creed, which Grundtvig had been troubled to meet with in “ An Exposition of the Creed” by John Pearson Bishop of Chester, a work otherwise approved of by the Danish divine. Hence it may be inferred that Grundtvig’s depreciation of Lutheranism in the Easter sermon represents a passing phase in 1829. As the No.s 1-5 are here proved to date from December 1828, only eleven sermons are left for originating from the early weeks of 1831, or a few of them from December 1830. The established fact that most of the sermons had been handed over to the printer more than three months before Grundtvig’s third departure for England, raises a question concerning other literary activities of his during that period. Part of the time was given to the preparation of his intended edition of Anglo- Saxon literature, but he paid no small attention to contemporary Danish literature, if partly against his will. The best-seller of that winter was Gjen102 ganger-Breve (“ Epistles from the Ghost” ), an anonymous cycle of rhymed epistles pretending to be sent from Paradise by the late Jens Baggesen; eighteen months later Henrik Hertz acknowledged the authorship, but so far nobody had attributed the book to him. It was a manifesto in favour of Johan Ludvig Heiberg, his classical taste and French sympathies, but a severe attack on Carsten Hauch, the chief advocate of German romanticism. Grundtvig thought little of either and did not care for their controversy; he was only concerned with the book as a document of the age. After overcoming an immediate religious shock at it, he regarded it mainly as an offence to his late fellow poet, and composed 38 lines of a parody. While he could belittle this idle work by an unknown poet, he felt less at ease with Huldre-Gaverne (“ The Elf’s Gifts” ), a novel combining idealism and satire by B. S. Ingemann, his only friend among contemporary poets. His first letter to Ingemann after he had been presented with it, is lost, but seems to have been somewhat harsh, and for the time being their literary achievement took different courses. Whereas Ingemann entered upon a crusade against science, the university, and literary criticism, Grundtvig was intent on regaining his natural, if lost, reputation. He did not want to get involved with Ingemann’s cause, which eventually led to conflicts with the historian Christian Molbech and the physicist H. C. Ørsted, former antagonists of his own, with whom he was now so well reconciled that they provided him with letters of introduction to their influential friends in England. Because of the extremely close resemblance to his own past life, particularly the years 1812- 15, Grundtvig must have felt it a most trying experience to witness Ingemann in his rage. More than anything else, this is likely to have persuaded him to grasp the hand of reconciliation proffered him by Adam Oehlenschlager, the grand old man of Danish literature, who felt no less alien from most of the young poets. As opposed to Ingemann’s sympathy with some members of the younger generation, the aim of Grundtvig was to promote an alliance of old poets of established fame: Oehlenschlager, Ingemann, and himself. Before he started on his third journey to England, Grundtvig had set his future course as a man of letters by adopting this attitude, and had revealed to his contemporaries the characteric outlook which he retained for the rest of his life.